PDL2+ CD11b+ dermal dendritic cells capture topical antigen through hair follicles to prime LAP+ Tregs. Issue 1 (December 2018) - Tordesillas, Leticia; Lozano-Ojalvo, Daniel; Dunkin, David; Mondoulet, Lucie; Agudo, Judith; Merad, Miriam; Sampson, Hugh; Berin, M.
Abstract The skin immune system must discriminate between innocuous antigens and pathogens. Antigen applied topically using a Viaskin® patch elicits immune tolerance that can suppress colitis and food allergy. Here we show how topical antigen is acquired and presented by dendritic cells in the skin. Topical antigen is acquired by Langerhans cells (LC) and CD11b+ cDC2s but not cDC1s, and both  LCs and CD11b+ cDC2s reaching the lymph node can prime T cells and expand LAP+ Tregs. However,  LCs are neither required nor sufficient for T cell priming, and have no role in tolerance induction. Conversely, IRF-4-dependent cDC2s are required for T cell priming. Acquisition of antigen in the dermis, delivery to the draining lymph node, and generation of tolerance are all absent in hairless mice. These results indicate an important function for hair follicle niche and CD11b+ cDC2s in antigen acquisition, and in generation of primary immune tolerance to topical antigens. Antigen present and presented in the structures of the skin can result in immune responses that elicit tolerance, protective immunity or allergy, depending on the immunological context. Here the authors describe a key role for the hair follicle and CD11b+ dendritic cells in the priming of local antigenic tolerance.